Utility of Flexible Bronchoscopy in Intensive Care Unit: Experience of Türkiye Yüksek İhtisas Education and Research Hospital - Sema Turan; İhsan Ayık; Candan Haytural; Dilan Akyurt; Berna Ergün; Soner Yavaş; Bülent Yamak; Özcan Erdemli (Galenos Yayinevi, 2010)
Objective: Fiberoptic bronchoscopy (FOB) is the most frequently used tool for invasive pulmonary evaluation with high diagnostic yield and low incidence of major complications. These advantages led to increasing use of FOB in intensive care units. In this article, we discussed our experiences of FOB applications in mechanical ventilated critically ill patients. Materials and Methods: We investigated FOB procedures of 118 patients on mechanical ventilation for respiratory failure in intensive care unit retrospectively. All patients' demographic data, indications, complications and arterial blood gas analyses belong to before and after bronchoscopy were evaluated. Results: FOB indications of the patients were 55.1% for mucoid plug clearance, 9.3% for treatment of atelectasia, 7.6% for identifying hemorrhagic foci, 17.8% for tracheostomy management, 6.8% for bronchoalveolar lavage and 3.4% for exploratory purposes. Overall complication rate of FOB was 11.9%. Arterial blood gas analyses statistically improved after FOB. Conclusion: In this study, we observed that FOB is being performed with many different indications and acceptable complication rates in our intensive care unit and also contributes to diagnose and treatment of intensive care patients. (Journal of the Turkish Society of Intensive Care 2010; 8: 48-53)